Optical properties of metal oxides based nanofluids - Said, Z.; Saidur, R.; Rahim, N.A. (Elsevier, 2014)
The purpose of this research is to experimentally investigate optical behavior of alumina and titania nanofluids. In this study, classical theories such as, Rayleigh, Maxwell-Garnett and Lambert-Beer's approaches are used for analytical analysis. The effect of surfactant on stability of nanofluids has been examined. Experiment is conducted for two volume concentrations of 0.1% to 0.3% v/v for the optical properties. Both experimental and analytical analyses were used to obtain these properties of nanofluids. Extinction coefficient and refractive index of TiO2 nanofluids are found higher than Al2O3 nanofluids in visible region of light for all concentrations. Results of this work will be very helpful in analyzing direct absorption solar collectors using alumina and titania nanofluids. (C) 2014 Elsevier Ltd. All rights reserved.